The results of German European policy under Angela Merkel (2005–2017) - Koszel, Bogdan (Wydział Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2017)
During the three administrations of Chancellor Angela Merkel, Germany has become an unquestioned leader of the European Union. Owing to its enormous economic capacity and the weaknesses of its main partners – France and the United Kingdom – Germany managed to enforce its own solutions to the financial crisis in the eurozone and resolving the conflict in Ukraine. It was highly problematic, however, to Europeanize the problem of immigrants, and the Euroconstitution and the implementation of the European Neighbourhood Policy should be viewed as failures.

W okresie rządów trzech gabinetów kanclerz A. Merkel Niemcy stały się niekwestionowanym liderem Unii Europejskiej. Dzięki olbrzymiemu potencjałowi gospodarczemu i słabości najważniejszych partnerów Francji i Wielkiej Brytanii udało się im narzucić swoje rozwiązania w kwestii wyjścia z kryzysu strefy euro i rozwiązania konfliktu na Ukrainie. Z dużą trudnością przyszło im jednak doprowadzenie do europeizacji problemu uchodźców. Raczej o porażkach można było mówić w kwestii Eurokonstytucji i realizacji Europejskiej Polityki Sąsiedztwa.
Bilans polityki europejskiej Niemiec pod rządami Angeli Merkel (2005–2017)
Keywords: Merkel; Germany; European policy; European Union; Merkel; Niemcy; polityka europejska; Unia Europejska